ANALISIS LOYALITAS PADA MEREK : SEBUAH KAJIAN PERAN KEPERCAYAAN DAN KEPUASAN PADA MEREK - Prabawani, Bulan; Saryadi, Saryadi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2007)
This research aims to examine factors that generate brand loyalty of cellular phone consumption, which will focus on correlation of two variables, brand trust and brand satisfactions and brand loyalty, and then followed by examination of correlation of brand satisfactions and brand loyalty through the brand trust as an intervening variable. Using the concept of trust from Deutsh (Lau and Lee, 2000) and the concept of loyalty from Assael (1998); this research examines 100 users of cellular phone in Semarang that has the experience of consuming two different brand of cellular phone in 2006. The result shows that brand satisfactions have a direct correlation with brand loyalty, but moderately weaker compare to the correlation between brand satisfactions through brand trust as an intervening variable.